Fantasmes de la tradició Sobre l'assaig contemporani i les seues arrels en l'edat moderna. - LÓPEZ-PAMPLÓ RIUS, GONÇAL (Scripta)
Our aim is to establish several lines of continuity between the European essay of Modern Age and the development of Catalan contemporary essay, with the appearance of Eugeni d'Ors' Glosari (1906) as the main milestone. Thus, we will analyse the formal models and literary referents available at the turn of the 19th and 20th centuries, with special attention to the French and German-based essayistic tradition, considering both Enlightenment and Romanticism. Then, we will focus on the material conditions in which these texts were written, published and read, above all with regard to the development of mass media and contemporary publishing industries, factors that facilitated the emergence of intellectuals as a social figure. Finally, we will examine how contemporary essay dialogues with its own tradition, both in linguistic and literary terms.